Changes in the temperature and precipitation extremes in China during 1961–2015. (30th August 2019) - Shi, Jun; Cui, Linli; Wang, Junbang; Du, Huaqiang; Wen, Kangmin
Abstract: Based on daily maximum temperature (Tmax), daily minimum temperature (Tmin) and daily precipitation collected from 1867 meteorological stations in China from 1961 to 2015, the spatiotemporal variations in temperature and precipitation extremes and their associations with large-scale atmospheric and oceanic circulation patterns were analyzed using linear trend analysis, Pearson correlation analysis and Mann-Kendall method. Results indicate that both the maximum Tmin (TNx) and the minimum Tmin (TNn) had increased significantly at rates of 0–0.5 °C and 0.2–1.0 °C per decade respectively in most of China, whereas the trends in the maximum Tmax (TXx) and the minimum Tmax (TXn) were not significant, resulting in a decrease of diurnal temperature range (DTR) at rates of 0–0.7 °C per decade in most of northeastern China, northern China and western China. The percentage changes in TXn and TNn were much higher than those of TXx and TNx. For precipitation indices, simple daily intensity index (SDII) and extremely wet-day precipitation (R99p) had increased at rates of 0.10 mm/day and 2.6 mm per decade respectively, but the trends of maximum 1-day precipitation (Rx1day), maximum 5-day precipitation (Rx5day) and total wet-day precipitation (PRCPTOT) were not significant in China. The spatial trends of five precipitation indices were also not significant in almost the whole of China. Higher percentage changes of precipitation indices were mainly appeared in western China. Most of climatic indices had positive correlation with Atlantic multidecadal oscillation (AMO) and negative correlation with East Atlantic/Western Russia (EA/WR). The variations of TXx and TNx were more related to the variability of AMO and EA/WR in China, and those of TXn and TNn were more associated with the Arctic oscillation (AO) in northeastern China, northern China and northern Xinjiang. The variations of precipitation indices were not significantly related to the circulation patterns in the vast majority of China.